¿Suscribió santo Tomás de Aquino la tesis según la cual el mundo pudo haber existido desde siempre? Una respuesta a Wippel y Bukowski (2025)
Regarding the topic of the eternity of the world, the following position is often attributed to St. Thomas Aquinas: that the world, in fact, had a beginning, but could have always existed. However, in none of Aquinas' texts can an explicit defense of the possibility of an eternal world be found. Nevertheless, at least two authors, John F. Wippel and Thomas Bukowski, offer a systematic defense in favor of such attribution. This paper argues for the opposite, namely, that it is inaccurate to attribute to Aquinas the claim that the world could have always existed. For this, the argumentation of the two aforementioned authors is reviewed step by step, and a counterargument for both is presented. The paper then turns to the distinction that Aquinas himself makes regarding the various senses of "possible" in article 14 of De potentia. This distinction is used to complement Giles of Rome's framework in order to provide greater clarity regarding Aquinas' precise stance on the possibility of an eternal world.